Spatial-Temporal Analysis of Dengue Hemorrhagic Fever (DHF) in Kendari City 2014-2018 - Sri Aprilianti Idris; Muhammad Sultanul Aulya (Jurnal Profesi Medika : Jurnal Kedokteran dan Kesehatan, 2020)
This study aims to determine the spatiotemporal pattern of cases of dengue hemorrhagic fever (DHF) in Kendari City during 2014 - 2018 and to see the correlation of cases of dengue hemorrhagic fever (DHF) with rainfall, larva free index (LFI) and population density in Kendari city. This study uses an ecological study design that is analytic or an analytic observational study. Sampling in this study was carried out by total sampling, so the sample in this study were residents who suffered from dengue hemorrhagic fever (DHF) microcopically which was integrated in the monthly reports of cases of dengue hemorrhagic fever (DHF) at the Kendari City Health Office during 2014-2018, namely totaled 1,406 people. This research was conducted in August-October 2020. The data were analyzed temporally (graphically) and statistically using the Spearman-rho correlation test. The data were processed using GeoDa 1.6.7, QuantumGIS 10.3 and IBM SPSS version 20 programs. The study showed that the spatial pattern of cases of dengue hemorrhagic fever (DHF) in Kendari city showed a random pattern (Moran's index = 0.47745). The temporal trend of DHF cases increases at the beginning of the year entering the rainy season (January - July) and decreases at the end of the year after the rainy season (August - December). Based on the statistical test, there was a significant correlation between rainfall (p = 0.000 <0.05) and the incidence of dengue fever and there was no significant correlation between larvae free rate (p = 0.502> 0.05); population density. (p = 0.440> 0.05) with the incidence of DHF.